2004
DOI: 10.1128/cdli.11.2.325-329.2004
|View full text |Cite
|
Sign up to set email alerts
|

Heterophile Antibody Interference in a Multiplexed Fluorescent Microsphere Immunoassay for Quantitation of Cytokines in Human Serum

Abstract: While modern immunoassays provide sensitive and specific means for the quantitation of cytokines in biological fluids, heterophile antibodies are still a well-recognized cause of interference in the measurement of cytokines in these assays. We have developed a multiplexed fluorescent microsphere immunoassay for the simultaneous quantification of 10 cytokines in only 75 l of serum. During the development of this multiplexed assay, the amount of assay interference due to heterophile antibodies was also determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…Previous studies have reported inhibition of detection for specific cytokines in the context of serum [6–10]. In recent years, vendors of immunoassay kits have in fact taken into account this phenomenon by diluting cytokine standards in a buffer that mimics the serum matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported inhibition of detection for specific cytokines in the context of serum [6–10]. In recent years, vendors of immunoassay kits have in fact taken into account this phenomenon by diluting cytokine standards in a buffer that mimics the serum matrix.…”
Section: Resultsmentioning
confidence: 99%
“…This makes it difficult to detect small changes in their abundance that may accompany a disease state. Furthermore, previous studies have shown that serum and plasma themselves inhibit the detection of many cytokines, as shown by spike recovery experiments [6–10]. This so-called matrix inhibition can be due to specific and non-specific factors and varies by cytokine.…”
Section: Introductionmentioning
confidence: 95%
“…The serological Luminex assays were developed using a standard sandwich capture format (27, 28). Briefly, monoclonal antibodies to human sCD14 (clone 55-3, BD Pharmingen, San Diego, CA) or sCD23 (clone 138633, R&D, Minneapolis, MN) were coupled to carboxylated Luminex microspheres by using a two-step carbodiimide reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokine levels were measured using a multi-analytic fluorescent detection method in contrast to the more familiar enzyme linked immunosorbent assays (ELISA) 38 . This procedure allows the simultaneous detection of multiple serum cytokines as opposed to ELISA assays that detect one cytokine per assay.…”
Section: Methodsmentioning
confidence: 99%